Moral Risk in the Behavior of Doctors of the Comprehensive Health Insurance in the Province of San Román, Puno-Peru, 2021 - Quispe Mamani, Julio C.; Quilca Soto, Yessica; Calcina Álvarez, Dominga A.; Yapuchura Saico, Cristóbal R.; Ulloa Gallardo, Nelly J.; Aguilar Pinto, Santotomas L.; Quispe Quispe, Betsy; Quispe Maquera, Nelly B.; Cutipa Quilca, Balbina E. (Frontiers in Public Health, 2022)
Objective The objective of the research was to determine which socioeconomic factors are the ones that most influence the moral hazard in the behavior of the doctors of the Comprehensive Health Insurance in the province of San Román and to identify the attitude of the doctor to a gift and its influence in moral hazard. Methods The methodology used has a mixed, non-experimental and correlational approach, the Binomial Probit econometric model was used, applying a survey to 32 active doctors who work in the different SIS centers. Results It is concluded that the factors that influenced the moral hazard and the behavior of the doctors were the bad reputation with a positive relation (27%), the social pressure with a negative relation (98%) and the behavioral attitude with a positive relation (94 %). Conclusions Of the survey carried out, 40.6% of doctors reject the offer of a gift or bribe, reducing the influence of moral hazard by 94%.